Sports infrastructure as a training environment: Participation patterns and adherence challenges in rural municipalities - David Cobos-Valiente; Jerónimo García-Fernández; Moisés Grimaldi-Puyana (CV. FOUNDAE, 2026)
Background: Rural areas face persistent challenges in promoting regular sports participation due to demographic ageing, limited infrastructure, and uneven access to organized programs. These constraints may affect not only population-level physical activity but also the training environments available to athletes and coaches in small rural municipalities. Aims: This study analyzes sports habits, motivations, barriers, and the availability of sports facilities in three rural municipalities in southern Spain, examining how local infrastructural and organizational conditions shape participation patterns and adherence to sport. Methods: A cross-sectional descriptive design was employed involving 289 residents from Cumbres Mayores, Cumbres de San Bartolomé, and Cumbres de Enmedio, selected through a non-probabilistic snowball sampling technique. Data were collected using an adapted questionnaire based on the Spanish Survey of Sports Habits, consisting of items on sports participation frequency, motivations, perceived barriers, and assessment of local sports facilities. The questionnaire demonstrated adequate content validity through expert judgment and high internal reliability (Cronbach’s α = 0.86). Data were analyzed using descriptive and comparative statistical procedures, including frequencies and percentages, to identify inter-municipal patterns. Result: The findings reveal apparent inter-municipal differences in sustained sports participation and perceived facility adequacy. More than one-third of respondents reported not engaging in regular physical activity, while insufficient or poorly maintained facilities were identified as a key barrier by over 30% of inactive participants. Approximately 40% indicated having practiced sport in the past but no longer do so, particularly in the smallest municipality, suggesting adherence challenges rather than a lack of initial interest. Gender-related disparities were also observed, mainly associated with time constraints and limited program availability among women. Notably, over 70% of participants expressed willingness to resume or increase participation if access to facilities and guided programs improved. Conclusion: Sports participation in small rural contexts depends not only on individual motivation but also on the availability, accessibility, and activation of local sports infrastructure. For athletes and coaches, these conditions directly affect training continuity, program viability, and development opportunities. The results support the need for context-sensitive sports planning that integrates infrastructure improvement, supervised training, and community engagement to promote sustainable training environments in rural areas.